Mephentermine Dependence in a Young Athlete: Case Report With Review of Literature. Issue 4 (July 2017) - Singh, Swarndeep; Gupta, Ankit; Sarkar, Siddharth
Abstract : N/A: Mephentermine is structurally related to amphetamines and is banned for its use as a performance-enhancing drug in competitive sports. Limited literature is available on management of mephentermine dependence. Here, we describe a case of mephentermine dependence followed by review of literature and a discussion about its management. A 20-year-old professional wrestler presented with high-dose intravenous mephentermine use, and rapid development of dependence, in the absence of any comorbid substance use or psychiatric disorder. The client showed improvement with bupropion and individual counseling sessions. The present report highlights the need to explore effective treatment options for individuals who have been addicted to mephentermine.